Primary Biliary Cirrhosis: Overlaps with Other Autoimmune Disorders - Floreani, Annarosa; Franceschet, Irene; Cazzagon, Nora (Seminars in Liver Disease, 2014)
In this article, the authors use the term “overlaps” to refer to the coexistence of primary biliary cirrhosis (PBC) with another autoimmune condition that involves the liver or extrahepatic organs. Diagnosing PBC-autoimmune hepatitis (PBC-AIH) overlap syndrome remains a challenge, especially because there is still no consensus on the most appropriate diagnostic criteria. The prevalence of this condition varies considerably among series of PBC patients, and its treatment demands a combination of ursodeoxycholic acid and immunosuppressive drugs. Overlap syndrome between PBC and primary sclerosing cholangitis is described in exceptional cases. About one in three PBC patients have a concomitant extrahepatic autoimmune disease, which may include rheumatological, endocrinological, gastrointestinal, pulmonary, or dermatological conditions. Overlaps raise several questions, about whether they share much the same genetic susceptibility, as is generally assumed. The pathogenesis of these conditions includes the production of both innate and adaptive immune responses targeting cholangiocytes as well as different extrahepatic tissues. In this sense, overlaps in PBC represent a continuous spectrum of autoimmunity involving liver and extrahepatic tissues.
Keywords: primary biliary cirrhosis; autoimmune hepatitis; overlap syndrome; Sjögren syndrome; Hashimoto thyroiditis